Anterior Skull Base Analysis from Coronal and Reconstructed Computed Tomography: Radio-Anatomical Study (Nepal Medical College Journal, 2021)
Endoscopic sinus and skull base Surgery has gained significant improvement widely all over the world. A computerized tomography (CT) scan provides a detailed anatomy of the skull base especially the bone framework. This study aims to analyze the fixed anatomical bony landmarks of the anterior skull base through coronal and reconstructed CT in the context of the Nepalese population and guide the surgeon to perform endoscopic sinus and skull base surgery safely. This Prospective study includes 70 Computerized Tomography scans of Paranasal sinuses. The different measurement from nasal floor to skull base was taken in coronal and reformatted sagittal CT scan. Mean, standard deviation, minimum and maximum values were analyzed using descriptive statistics. Student T-test was applied to compare between right and left side. This study includes 75 patients between 18 to 77 years. The measurement from nasal floor to the cribriform plate and ethmoidal roof in right and left side were, mean± SD (47± 4.1, 45.3±4.3, 47.9±5.1, and 49±8.5 mm) respectively. Mean Take off angle at the cribriform plate was 43.9 ±10.9°on right side and 43 ± 9.4° on the left side. The distance from the nasal spine to the skull base (mean ± SD) at nasofrontal recess, bulla ethmoidalis, and the junction of sphenoethmoid levels at right sides were 51.5 ± 4.7, 52.9 ± 4.1, and 61.2 ±4.7 little higher at left side. This study provides a detailed analysis of the anterior skull base in coronal and sagittal CT scans which helps to reduces complications.